2015
DOI: 10.3389/fmicb.2015.01240
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Genotypic Diversity of Campylobacter Isolated from Pigs, Dairy, and Beef Cattle in Tanzania

Abstract: Foodborne Campylobacter infections pose a serious threat to public health worldwide. However, the occurrence and characteristics of Campylobacter in food animals and products remain largely unknown in Tanzania. The objective of this study was to determine the prevalence, antibiotic resistance, and genetic profiles (sequence types, STs) of Campylobacter isolated from feces of pigs and dairy and beef cattle in Tanzania. Overall, 259 (~30%) of 864 samples were positive for Campylobacter spp, which were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 62 publications
6
31
1
3
Order By: Relevance
“…Another study on sheep and goats in Grenada by Stone et al (2014) revealed resistance of Campylobacter isolates to tetracycline (30.8%, 4/13), which is also significantly lower ( p = 0.005) than the observation in this study. Other studies in different geographical areas have also shown a low resistance rate of Campylobacter isolates from different animals and humans to tetracycline in comparison with our observation (Moore et al, 2006;Kashoma et al, 2015). On the other hand, other studies have reported high resistance rates of Campylobacter isolates from animals and humans to tetracycline, which is in close agreement with the observation in this study (Hariharan et al, 1990;Rollo et al, 2010;Scott et al, 2012;Stone et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Another study on sheep and goats in Grenada by Stone et al (2014) revealed resistance of Campylobacter isolates to tetracycline (30.8%, 4/13), which is also significantly lower ( p = 0.005) than the observation in this study. Other studies in different geographical areas have also shown a low resistance rate of Campylobacter isolates from different animals and humans to tetracycline in comparison with our observation (Moore et al, 2006;Kashoma et al, 2015). On the other hand, other studies have reported high resistance rates of Campylobacter isolates from animals and humans to tetracycline, which is in close agreement with the observation in this study (Hariharan et al, 1990;Rollo et al, 2010;Scott et al, 2012;Stone et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…In the Campylobacteriaceae, C. coli, C. fetus, and C. jejuni were detected in cow rumen fluid and feces (Table 1). Similar findings were reported in Tanzania, Kenya and Ghana by (Kashoma et al, 2015;Nguyen et al, 2016;Karikari et al, 2017) in beef cattle feces, faeces and cloacal swabs of chickens and faeces and carcasses of healthy livestock animals, respectively. Pathogenic bacteria Staphylococcus aureus and Staphylococcus sciuri were detected only at the smallholder farms in Tanzania (Table 1).…”
Section: Blaaccsupporting
confidence: 87%
“…The difference in AMR gene abundances also was observed between the isolates identified at the station and onfarms (Table 2). This difference could be due to differences in geographical locations, environment, management, farming practices, and concentration of the farms in the locations as reported by Kashoma et al (2015) and Nyabundi et al (2017). Additionally, the samples originating from different environment display different AMR gene abundance as reported by Gerzova et al (2015).…”
Section: Blaaccmentioning
confidence: 93%
“…1, which revealed that gentamicin resistance was much more prevalent in C. coli than in C. jejuni isolates (P Ͻ 0.0001, Fisher's exact test). Generally, the rate of resistance of Campylobacter to gentamicin is low (Ͻ2%) in other countries (8,18,19). However, recent studies performed in China suggested that the frequency of gentamicin resistance is high in Campylobacter, especially in C. coli isolated from swine and broiler chickens (23.2% to 95.4%) (10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
“…In general, gentamicin resistance rates in Campylobacter have been reported to be low and stable in most countries (5)(6)(7)(8). In the United States, gentamicin resistance in Campylobacter was rarely reported before 2007 according to National Antimicrobial Resistance Monitoring System (NARMS) studies; however, an increasing trend of resis-tance to aminoglycosides was observed in recent years (9).…”
mentioning
confidence: 99%